1997
DOI: 10.1007/pl00009182
|View full text |Cite
|
Sign up to set email alerts
|

On Triangulating Planar Graphs under the Four-Connectivity Constraint

Abstract: Triangulation of planar graphs under constraints is a fundamental problem in the representation of objects. Related keywords are graph augmentation from the field of graph algorithms and mesh generation from the field of computational geometry. We consider the triangulation problem for planar graphs under the constraint to satisfy 4-connectivity. A 4-connected planar graph has no separating triangles, i.e., cycles of length 3 which are not a face.We show that triangulating embedded planar graphs without introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In this section, we show that testing the existence of such drawings is NP-complete. This is in contrast with closed planar RI drawings, for which Biedl et al [4] present a polynomial time algorithm to find a closed RI-drawable embedding if one exists. The reduction presented here is based on the one by Garg and Tamassia [7] used for proving NP-hardness of finding orthogonal drawings of a given planar graph.…”
Section: Hardness Of Testing Ri-drawability Of Planar Graphsmentioning
confidence: 99%
“…In this section, we show that testing the existence of such drawings is NP-complete. This is in contrast with closed planar RI drawings, for which Biedl et al [4] present a polynomial time algorithm to find a closed RI-drawable embedding if one exists. The reduction presented here is based on the one by Garg and Tamassia [7] used for proving NP-hardness of finding orthogonal drawings of a given planar graph.…”
Section: Hardness Of Testing Ri-drawability Of Planar Graphsmentioning
confidence: 99%
“…We propose a reduction from the mis-3p problem which is known to be NP-complete [4]. The mis-3p problem consists in, given a cubic planar bridgeless connected graph G = (V, E) and an integer k, finding an independent set of size k in G. Recall, that a graph G = (V, E) is said to be cubic planar bridgeless connected if any vertex of V has degree three (cubic), G can be drawn in the plane in such a way that no two edges of E cross (planar), and there are at least two edge-disjoint paths connecting any pair of vertices of G (bridgeless connected).…”
Section: The Mapcs Problemmentioning
confidence: 99%
“…Indeed many graphs, including 4-connected plane graphs with at least 4 border vertices, can be triangulated (after adding 4 vertices in the outer face) into an irreducible triangulation of the 4-gon, see [1]. By investigating a bijection with ternary trees, we have observed that each irreducible triangulation of the 4-gon can be endowed with a structure, called transversal edge-partition, which can be summarized as follows.…”
Section: é Fusymentioning
confidence: 99%